65‐1: Invited Paper: Characterizing High Dynamic Range Display System Properties in the Context of Today's Flexible Ecosystems. Issue 1 (May 2016) - Kunkel, Timo; Spears, Stacy; Atkins, Robin; Pruitt, Tyler; Daly, Scott
Abstract : The transition from standard dynamic range (SDR) imaging systems whose characteristics were largely derived from the capabilities of CRT displays is well underway toward a newer ecosystem with higher capabilities. The newer ecosystem improves color volume aspects such as high dynamic range (HDR) and wide color gamut (WCG), as well as improvements in other dimensions such as bit‐depth, spatial resolution, energy, thermal management, field‐of‐view, mobility, and frame rate. More importantly, since there will not be one single predominating display technology, a large variability of color volumes will result. Thus, the newer ecosystem needs to tailor the imagery to the specific display. Achieving such an ecosystem that includes flexible delivery methods such as the internet, broadcast, and solid‐state memory‐based storage media, displays must be characterized much more completely than they have for previous broadcast and disc‐based storage media ecosystems standards. This paper focuses on the color volume aspects (HDR, WCG) of such needed characterization, as well as key spatial aspects that relate to modern single and dual modulation display technology and power saving.